2015
DOI: 10.1021/acs.est.5b00679
|View full text |Cite
|
Sign up to set email alerts
|

World-Wide Indoor Exposure to Polyfluoroalkyl Phosphate Esters (PAPs) and other PFASs in Household Dust

Abstract: Human exposure to perfluorooctanoic acid (PFOA) and other per- and polyfluoroalkyl substances (PFASs) is ongoing and in some cases increasing, despite efforts made to reduce emissions. The role of precursor compounds such as polyfluorinated phosphate esters (PAPs) has received increasing attention, but there are knowledge gaps regarding their occurrence and impact on human exposure. In this study, mono-, di-, and triPAPs, perfluorinated alkyl acids (PFAAs), saturated, and unsaturated fluorotelomer carboxylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 44 publications
7
61
1
Order By: Relevance
“…The congener pattern of PFAAs in dusts was consistent with that in surface water and sediment in this area, in which PFOA and short chain PFCAs dominated as well (Wang et al, 2016). Like the congener pattern in the present study, PFOA was found to be the predominant PFCA in many other countries, such as Canada, Sweden, Spain or Australia (Eriksson and Kärrman, 2015). The median concentration of PFOA (852 ng/g) in house dust here was 1-2 orders of magnitude higher than that in house dusts from these countries (9-21 ng/g) (Eriksson and Kärrman, 2015) and was also 4 times higher than the mean PFOA concentration (205 ng/g) in indoor dusts from ordinary houses without a nearby point source in China (Zhang et al, 2010).…”
Section: Pfaas In Indoor Dustssupporting
confidence: 86%
See 1 more Smart Citation
“…The congener pattern of PFAAs in dusts was consistent with that in surface water and sediment in this area, in which PFOA and short chain PFCAs dominated as well (Wang et al, 2016). Like the congener pattern in the present study, PFOA was found to be the predominant PFCA in many other countries, such as Canada, Sweden, Spain or Australia (Eriksson and Kärrman, 2015). The median concentration of PFOA (852 ng/g) in house dust here was 1-2 orders of magnitude higher than that in house dusts from these countries (9-21 ng/g) (Eriksson and Kärrman, 2015) and was also 4 times higher than the mean PFOA concentration (205 ng/g) in indoor dusts from ordinary houses without a nearby point source in China (Zhang et al, 2010).…”
Section: Pfaas In Indoor Dustssupporting
confidence: 86%
“…The EDI of PFOA was 0.43 ng/kg·bw/day for adults and 5.3 ng/kg·bw/day for children in Birmingham, UK (Goosey and Harrad, 2011) and was 0.20 ng/kg·bw/day for adult women in Norway (Haug et al, 2011b). The estimated intake of PFAAs (PFOA) via dust ingestion by 2 years' children was between 2.5 (0.06) and 7.0 (0.11) ng/kg·bw/day in Australia, Canada, the Faroe Islands and Japan, 0.3-0.8 (0.04-0.06) ng/kg·bw/day in Greece, Spain, and Sweden, and 0.02 (0) ng/kg·bw/day in Nepal (Eriksson and Kärrman, 2015). Overall, the estimated intakes of PFOA/PFAAs by residents about 2 km and 5 km from the FIP in our study were highest compared with the values previously reported.…”
Section: Human Exposure To Pfaas Via Dust Ingestion and Dermal Absorpmentioning
confidence: 96%
“…Another potential source of intake of these compounds by humans, still not well researched, is dust (D'Hollander et al, 2010;Eriksson and Kärrman, 2015). Dust as a significant source of exposure may be the case for North American and some Asian countries (Fromme et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…and Shigeo FUJII 1) 1) Graduate School of Global Environmental Studies, Kyoto University, Yoshida honmachi, Sakyo-ku, Kyoto, 606-8501, Japan 2) Graduate School of Engineering, Kyoto University, Yoshida honmachi, Sakyo-ku, Kyoto, 606-8501, Japan…”
Section: )mentioning
confidence: 99%